Molecular Imaging of Mesothelioma with T99mc-ECG and G68a-ECG. (8th May 2012) - Zhang, Yin-Han; Bryant, Jerry; Kong, Fan-Lin; Yu, Dong-Fang; Mendez, Richard; Edmund Kim, E.; Yang, David J.
Abstract : We have developed ethylenedicysteine-glucosamine (ECG) as an alternative to 18 F-fluoro-2-deoxy-D-glucose ( 18 F-FDG) for cancer imaging. ECG localizes in the nuclear components of cells via the hexosamine biosynthetic pathway. This study was to evaluate the feasibility of imaging mesothelioma withT 99m c -ECG andG 68 a -ECG. ECG was synthesized from thiazolidine-4-carboxylic acid and 1, 3, 4, 6-tetra-O-acetyl-2-amino-D-glucopyranose, followed by reduction in sodium and liquid ammonia to yield ECG (52%). ECG was chelated withT 99m c /tin (II) andG 68 a / 69 Ga chloride for in vitro and in vivo studies in mesothelioma. The highest tumor uptake ofT 99m c -ECG is 0.47 at 30 min post injection, and declined to 0.08 at 240 min post injection. Tumor uptake (%ID/g), tumor/lung, tumor/blood, and tumor/muscle count density ratios forT 99m c -ECG (30–240 min) were0.47 ± 0.06 to0.08 ± 0.01 ;0.71 ± 0.07 to0.85 ± 0.04 ;0.47 ± 0.03 to0.51 ± 0.01, and3.49 ± 0.24 to5.06 ± 0.25 ; forG 68 a -ECG (15–60 min) were0.70 ± 0.06 to0.92 ± 0.08 ;0.64 ± 0.05 to1.15 ± 0.08 ;0.42 ± 0.03 to0.67 ± 0.07, and3.84 ± 0.52 to7.00 ± 1.42 ; for 18 F-FDG (30–180 min) were1.86 ± 0.22 to1.38 ± 0.35 ;3.18 ± 0.44 to2.92 ± 0.34, 4.19 ± 0.44 to19.41 ± 2.05 and5.75 ± 2.55 to3.33 ± 0.65, respectively. Tumor could be clearly visualized withT 99m c -ECG andG 68 a -ECG in mesothelioma-bearing rats.T 99m c -ECG andG 68 a -ECG showed increased uptake in mesothelioma, suggesting they may be useful in diagnosing mesothelioma and also monitoring therapeutic response.